Aislamiento, purificación y selección de bacterias como candidatos para ser utilizados en procesos de biorremediación de mancozeb (ethylenebisdiothio carbamate) utlizando en cultivos depapa - Pirahauta A, Miguel; Mojica, Martha; Baquero, Edgar (Revista Científica, 2006)
69 colonies of different bacteria were isolated in culture medium with mancozeb (0.0625mg/ml).They came from 28 samples of soil of potato crops. The isolated strains were cultivate for 24 hours at a temperature of 25 degrees celsius in salts broth, which was supplemented with sources of carbon (glucose 0.1%), nitrogen (potassium nitrate 0.2%) or without them and also with mancozeb (Dithane M 45 NT) in concentration of 0.0625mg/ml. Out of those 69 samples were selected and cultivate in this SGNM broth for 72 hours, incating possible use of mancozeb as an additional source of carbon. The bilogical activity of the strain called Pseudomonas putida upon mancozeb as a indicator of residual concentration of 0.0625mg/ml. Out of those 69 samples were selected and cultivate in this SGMN broth for 72 hours, indicating possible use of mancozeb as an additional source of carbon. The biological activity of the starin called Pseudomonas putida upon mancozeb was determined using a strain of Bacillus cereus sensitive to mancozeb as a indicato of resiudal concentration of mancozeb in the digestion means. It was detected that in 24h the strain P. putida with an initial population of 10 cells/ml degrade the mancozeb from 0.0625mg/ml. The speed of degration of the mancozeb with low P.putida population makes it promising for use in bioremediation of soil.